Kontribusi Usahatani Nilam terhadap Total Pendapatan Petani di Desa Sangia Tiworo Kecamatan Tiworo Selatan Kabupaten Muna Barat - Jati, Kirana Citra; Abdi, Abdi; Gafaruddin, Abdul (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2019)
The research aims at knowing: the total income of patchouli farming, and the contribution of patchouli farming towards the total income of patchouli farmers at Sangia Tiworo Subdistrict of South Tiworo, West Muna Regency. The population of the research is the entire farmers of patchouli and another kind of farming at Sangia Tiworo Subdistrict of South Tiworo, West Muna Regency which total 20 farmers. The technique of deciding sample is â€œProbability Random Samplingâ€ in which the entire farmers have an equal chance to be a sample. The data were analyzed by using â€œincome analysisâ€, and â€œcontribution formulaâ€. The result of the research shows total income of farmers per planting season is Rp. 435,620,298 on average Rp. 22,641,240. Patchouli farming gives a big contribution towards farmersâ€™ household income, which is being approximated at 31% - 97% on average contribution 84%.